KEBIJAKAN PENANGGULANGAN KRISIS EKONOMI DAN KONSEKUENSINYA TERHAPAP PELUANG PENINGKATAN PENDAPATAN PETANI - IRAWAN, BAMBANG (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
Economic crisis and various economic recovery policies issued by government lead to more dynamic and fluctuative prices of foodstuffs and agricultural inputs since mid 1997. During the peak period of the crisis food prices at retail market increased at higher rate, about 3 to 25 times of price growth before crisis, particularly for the low price foodstuffs. This means that the crisis tends to cause higher impact on food consumption of low income household. To overcome the crisis various trade policies on food and agricultural inputs issued by government so that the rate of growth of food prices become lower, in other word, favorable for food consumer. Those policies however were unfavorable for farmer’s income increase because due to policies on inputs trade the ratio of food prices to inputs prices decreased with increasing rate. The situation was more difficult for future agriculture development, which more focused on income increse instead of production increase, because in addition to unfavorable prices the crisis also lead to increase of number of people involved in agricultural sector about 3.56 million people or 9.9 persen. In order to support agriculture development, accordingly, reorientation and reorganisation of food trade policies for rice particularly is required.
Keywords: Economic Crisis, Economic Recovery Policies, Impact on food consumption, Low Income Household, Overcome the crisis, Reorientation and Reorganisation of Food Ttrade Policies